Fault diagnosis for rolling bearing based on VMD-FRFT. (April 2020) - Li, Xin; Ma, Zengqiang; Kang, De; Li, Xiang
Highlights: The definition and derivation of VMD-FRFT are given. VMD-FRFT is non-fragility to the center frequency of multicomponent LFM signal. VMD-FRFT is insensitive to the number of modes. VMD-FRFT is not only robust to noise, but also suitable for signals with low SNR. The validity of VMD-FRFT is verified by the fault diagnosis results of inner and outer rings of bearings. Abstract: In order to solve the problems that the fault feature of rolling bearing in early failure period is difficult to extract and the over-decomposition problem arises when applying the variational mode decomposition (VMD), in this paper, the fault diagnosis for rolling bearing based on variational mode decomposition–fractional Fourier transform (VMD-FRFT) is proposed. Firstly, based on the theory of fractional Fourier transform parameter estimation, the definition and derivation of VMD-FRFT are given and the modal component and center frequency estimation of the method are obtained. Secondly, the multicomponent linear frequency modulation (LFM) signal is simulated to verify the non-fragile to the center frequency distribution, the insensitive to the number of modes and the noise robustness of VMD-FRFT. Finally, VMD-FRFT is applied to the fault diagnosis of uniform acceleration rolling bearings, which can provide an effective filtering algorithm for the extraction of fundamental frequency and frequency multiplication of instantaneous frequency. Therefore, the VMD-FRFT proposed in this paper has certain reference significance for the fault diagnosis of rolling bearings.